Thinking about minimum wage increases in Alberta: Theoretically, Empirically, and Regionally - Marchand, Joseph; C.D. Howe Institute (C.D. Howe Institute, 2017)
Alberta's move to increase its minimum wage to $15 an hour by 2018 could lead to the loss of roughly 25,000 jobs. Alberta, being a boom and bust economy, would be better off taking current and future economic conditions into account when considering any future increases to its minimum wage.
OCLC: 1013494393